UTILITAS BISNIS ISLAM DALAM MANAJEMEN EKONOMI SYARIAH - Destiana, Yolanda (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Abstract This article discusses sharia economic management in Islamic business. This article uses the literature review approach method by comprehensively reviewing ideas and ideas from a scientific work in the form of books, journals or research. In running a business there are several basic principles that must be obeyed by business people. Based on the Al-Quran and hadith, every Islamic economic transaction is considered correct if there is no revelation that prohibits or regulates it. Management must be in accordance with the view of life and Islam. The Quran has provided instructions that can be used as the basis for building the science of Islamic business management. In the implementation of business implementation, it is necessary to support several principles of Islamic Economic management in doing business, namely, being able to be fair, being able to take responsibility for the business being undertaken, and being able to communicate well with fellow business people and customers so that functions in business can be implemented into Islamic economic management. Keywords : Management, Islamic business, Islamic business concepts, Islamic business functions.